2014
DOI: 10.1039/c4ra00741g
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of wood material properties via in situ polymerization of styrene into tosylated cell walls

Abstract: As an engineering material derived from renewable resources, wood possesses excellent mechanical properties in view of its light weight but also has some disadvantages such as low dimensional stability upon moisture changes and low durability against biological attack. Polymerization of hydrophobic monomers in the cell wall is one of the potential approaches to improve the dimensional stability of wood. A major challenge is to insert hydrophobic monomers into the hydrophilic environment of the cell walls, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 26 publications
6
40
0
5
Order By: Relevance
“…Even in latewood cell walls (thickness up to 10 lm) nearly the whole cell wall is filled with polymer (data not shown). These results support previous publications where it was shown that a so-called ''activation'' step is necessary to insert hydrophobic substances into the hydrophilic cell wall [14,15].…”
Section: Polymer Distribution In Woodsupporting
confidence: 94%
See 1 more Smart Citation
“…Even in latewood cell walls (thickness up to 10 lm) nearly the whole cell wall is filled with polymer (data not shown). These results support previous publications where it was shown that a so-called ''activation'' step is necessary to insert hydrophobic substances into the hydrophilic cell wall [14,15].…”
Section: Polymer Distribution In Woodsupporting
confidence: 94%
“…styrene) into the hydrophilic wood cell wall, with the evident disadvantage that such monomers show little penetration potential. Hence an activation step, which hydrophobizes cell wall components via reaction of the OH functionalities, is essential to improve the penetration of hydrophobic monomers in a second step [14,15]. Furthermore, the polymer chains should be covalently attached to the wood cell wall to achieve a stable modification without leaching of unbound chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, large efforts in chemical modification (Ermeydan et al, 2012;Trey et al, 2010;Ermeydan et al, 2014;Deka & Saikia, 2000;Jebrane et al, 2011;Yuan et al, 2013;Jebrane & SĂšbe, 2008) have been devoted to maintain permanent fixation of wood materials. Hydro-thermal treatment (Esteves & Pereira, 2009;Todaro et al, 2012;Lam et al, 2013;Tooyserkani et al, 2013) and thermohygro-mechanical treatment (Navi & Girardet, 2005;Welzbacher et al, 2008;Diouf et al, 2011;Cai et al, 2013) remain challenging and attractive since they are efficient and ecofriendly strategies to improve the dimensional stability and durability of wood.…”
Section: Introductionmentioning
confidence: 99%
“…See DOI: 10.1039/c4gc00194j a hydrophobic monomers inside wood, but very few of them report on the successful insertion of polymers inside the cell wall structure, and as a result, on an efficient improvement of dimensional stability. [11][12][13][14][15] Recently, our group reported on a wood pre-treatment enhancing the introduction of hydrophobic molecules within the cell wall. 16 We successfully inserted hydrophobic flavonoid molecules inside the cell walls, yielding a wood material with reduced water uptake as well as increased dimensional stability.…”
Section: Introductionmentioning
confidence: 99%